(untitled) - MAGDALENA ANALINDA DASAN, MARIA (LATERNE, 2013)
Language is a media needed for someone to communicate. One factor supporting foreign language to communicate well is vocabulary. The more vocabulary are controlled by a person, the communication skills possessed by the person, the better (Tarigan, 1982:2). Studying vocabulary is not only just but necessary to memorize the order memorized vocabulary stay memorable. Based on the experience of researchers for PPL in SMAN 14 Surabaya, vocabulary students have felt not maximized, particularly in reading skills. For that Lernetui media serve as one of the media used to study vocabulary. Formulation of the problem (1) How the application "Lernetui" as a medium of learning vocabulary for reading skills German language class XI IPA 3 SMAN 14 Surabaya? (2) How do the results of the use of Lernetui as a medium of learning vocabulary for reading skills German language class XI IPA 3 SMAN 14 Surabaya? Objective: (1) Describe the application Lernetui media as a medium of learning vocabulary for reading skills German language class XI IPA 3 SMAN 14 Surabaya (2) Describe the results of the use of media as a medium Lernetui vocabulary learning to read German language skills class XI student of SMAN 14 Surabaya . This research is a descriptive study with a qualitative approach. The study was conducted over four sessions. Meetings held the first and fourth pre-test and post-test. And on the second and third meetings of the learning process by using Lernetui media. Results: From the results of the application of media, almost the entire vocabulary of a given student can memorize. Application Lernetui media can be used if combined with media and media Lernbox is effectively used in reading skills. It is evident from the comparison of pre-test and post-test students. The average value of students in the pre-test 64.35, rose to 81.41 at post-test. Keywords: media Lernetui, vocabulary, reading.